Simulasi Pendinginan Baterai pada Kendaraan Konversi dengan Transmisi Otomatis - Yosua Setiawan; Adrian Sutjiadi (Department of Mechanical Engineering Atma Jaya Catholic University of Indonesia, 2026)
This study investigates the thermal behaviour of a converted electric vehicle battery pack under the NEDC and WLTP driving cycles using GT-Suite simulation. The results show that driving conditions significantly influence battery temperature. Under the NEDC cycle, the peak temperature reached 61°C without cooling, which decreased to 50.7°C with passive cooling and 30.1°C with active cooling. In contrast, the more demanding WLTP cycle produced higher thermal stress, with peak temperatures of 75.7°C without cooling and 66.5°C with passive cooling, while active cooling reduced it to 38°C. The findings indicate that rapid acceleration and high-speed operation increase discharge currents, leading to higher heat generation. Although passive cooling reduces thermal stress, it is insufficient to maintain safe operating temperatures under dynamic conditions, whereas active cooling provides effective thermal control. This study highlights the importance of battery thermal management in EV conversions and demonstrates the effectiveness of simulation tools for early-stage thermal evaluation.